Psychotic Patients’ Awareness of their Illness and its Correlates - Amal Gamal El-Din Shehata; Magdala Habib Farid Maximos (Journal of High Institute of Public Health, 2007)
Awareness about illness is defined in terms of a patient’s psychological attitude toward the psychiatric situation, and is to be evaluated from the standpoint of the person’s sick-role concept, by assessing the recognition of the need for treatment and acceptance of the treatment situation. Previous researches have suggested that lack of psychiatric patients’ awareness of their illness may have considerable power in predicting the long-term course of chronic mental disorders, and have an impact on patients compliance with treatment plans and relapses of psychosis. The aim of this study was to find out the psychotic patients’ awareness of their illness and its correlates. The results suggest that self-awareness deficits are a prevalent feature in mentally ill patients, perhaps stemming from the neuropsychological dysfunction associated with the disorders, and deficits in illness awareness are associated with greater number and longer duration of hospitalizations, and is considered one of the most important reasons for non-compliance.